Gastroparesis and Systemic Lupus Erythematosus: A Propensity Score‐Matched Study of US National Database Analysis - Noppachai Siranart; Pannathorn Nakaphan; Thanathip Suenghataiphorn; Panisara Fangsaard; Tanattida Phanthong; Patavee Pajareya; Somkiat Phutinart; Pawaris Tirakunwichcha; Suwit Paksin; Pornnicha Sowalertrat; Sakkarin Chirapongsathorn; Kittithat Tantitanawat (JGH Open)
ABSTRACT Introduction While gastrointestinal involvement is a common manifestation of systemic lupus erythematosus (SLE), the association between gastroparesis and SLE remains unclear. Methods We analyzed data from the National Inpatient Sample (NIS) database from 2016 to 2021. Patients with gastroparesis were categorized into SLE and non‐SLE groups. Similarly, patients with SLE were categorized into gastroparesis and nongastroparesis groups. Clinical characteristics, comorbidities, hospitalization data, and outcomes were compared. The primary outcome was the association between SLE and primary gastroparesis. Secondary outcomes were clinical impacts of gastroparesis in patients with or without SLE. Results A total of 12 538 228 patients were included from the NIS database. Of these, 1 165 925 patients (9.3%) were diagnosed with gastroparesis during hospitalization, while 11 372 303 patients (90.7%) did not have gastroparesis. SLE was significantly more common in patients with gastroparesis compared to those without (1.6% vs. 0.7%, p < 0.001; aOR 1.87 [95% CI: 1.80–1.95]). Among patients hospitalized with gastroparesis, those with SLE had a longer length of stay, with a β‐coefficient of 0.31 (95% CI: 0.07–0.55, p = 0.009), lower hospitalization charges, with mean differences of $4761 (95% CI: 442–9080, p = 0.031), and a higher rate of intervention needs, with odds ratios of 1.31 (95% CI: 1.09–1.56, p = 0.003). After propensity‐score matching (1:1), SLE patients aged ≥ 65 had higher hospital charges, with mean differences of $7287 (95% CI: 2928–11 646, p = 0.01), compared to non‐SLE patients. Conclusion Gastroparesis is associated with SLE, contributing to longer hospitalizations, higher costs, and increased need for invasive interventions. These findings underscore the importance of evaluating gastroparesis in SLE patients to enable early management and reduce potential complications.